Uji Aktivitas Antibakteri Kombinasi Ekstrak Daun Tebu (Saccharum officinarum L.) Dan Sari Kurma Terhadap Bakteri Salmonella typhi - chilyatus saadah; Cikra Ikhda Hamidah Safitri (Akademi Farmasi Yarsi Pontianak, 2023)
ABSTRACT Plants have many chemical components. There are many treatments using natural ingredients that can be chosen as a solution to overcome the disease. One of the many plants used as traditional medicine is the sugarcane plant (Saccharum officinarum L.) . Sugarcane leaves were extracted by maceration method using 70% ethanol then ttebu extract was added date palm juice in a ratio of 1: 1 and antibacterial testing was carried out against Salmonella typhi bacteria using disc diffusion method in concentration variations of 25%, 50%, 75%, 100%. This study aims to test the antibacterial activity of sugarcane leaf extract against Salmonella typhi bacteria, know the difference in antibacterial activity at several concentrations, and determine the minimum inhibitory level of extract. The results of this study showed a combination of sugarcane leaf extract and date palm juice concentration of 25%, 50%, 75%, 100% did not have an inhibition zone. The conclusion of this study proves that sugarcane leaf extract and date palm juice do not have antibacterial power against Salmonella typhi. Keywords: Salmonella typhi, sugar cane leaves, flavonoids, date palm juice